miR-424/322 protects against abdominal aortic aneurysm formation by modulating the Smad2/3/runt-related transcription factor 2 axis - Hsiao-Ya Tsai; Jen-Chun Wang; Yu-Juei Hsu; Yi-Lin Chiu; Chih-Yuan Lin; Cheng-Yo Lu; Shih-Hung Tsai (Elsevier, 2022)
Rupture of abdominal aortic aneurysms (AAAs) is one of the leading causes of sudden death in the elderly population. The osteogenic transcription factor runt-related gene (RUNX) encodes multifunctional mediators of intracellular signal transduction pathways in vascular remodeling and inflammation. We aimed to evaluate the roles of RUNX2 and its putative downstream target miR-424/322 in the modulation of several AAA progression-related key molecules, such as matrix metalloproteinases and vascular endothelial growth factor. In the GEO database, we found that male patients with AAAs had higher RUNX2 expression than did control patients. Several risk factors for aneurysm induced the overexpression of MMPs through RUNX2 transactivation, and this was dependent on Smad2/3 upregulation in human aortic smooth muscle cells. miR-424 was overexpressed through RUNX2 after angiotensin II (AngII) challenge. The administration of siRUNX2 and miR-424 mimics attenuated the activation of the Smad/RUNX2 axis and the overexpression of several AAA progression-related molecules in vitro. Compared to their littermates, miR-322 KO mice were susceptible to AngII-induced AAA, whereas the silencing of RUNX2 and the administration of exogenous miR-322 mimics ameliorated the AngII-induced AAA in ApoE KO mice. Overall, we established the roles of the Smad/RUNX2/miR-424/322 axis in AAA pathogenesis. We demonstrated the therapeutic potentials of miR-424/322 mimics and RUNX2 inhibitor for AAA progression.